"Bonum commune Ecclesiae" and the juridical domain of goods 'made common' in the Church - Popović, Petar 1983- (2019)
This paper re-evaluates the concept of bonum commune Ecclesiae in light of recent research on the original Thomistic meaning of the common good in the context of social ontology and the current re-reading of classical juridical realism. After distinguishing, as well as establishing the inherent connections between, the concept of the common good of the Church from other things or goods that are “made common” in the Church, the paper addresses the question of the juridical domain of bonum commune Ecclesiae.